(untitled) (Journal of Advanced Research in Social Sciences, 2025)
This paper employs a case study using familial patriarchal framework to contribute to the literature of first generation married Pakistani women’s experiences in Pakistani diaspora in Western Australia. Through a qualitative interpretive phenomenological approach, it highlights how these women navigate selective assimilation, striving to fulfill their marital aspirations while balancing familial and cultural expectations. Theoretically, this study builds on Gerda Lerner’s Paternalistic Dominance (PD) concept. The study’s aims were to: 1) emphasize on learned and cultural context of performing gender roles, 2) explain women’s divergent perspectives on PD, and 3) stress the importance of culturally competent social services for Pakistani immigrant women in diaspora. The study employed Braun and Clark’s (2021) thematic analysis to arrive at themes from the data that clustered in three sections: Traditional gender roles, Family values, and PD. The analysis was conducted from a feminist standpoint, which revealed that patriarchal ideologies, culture, and expected future and present securities through marital union influenced many women to reproduce gendered inequality. Women’s narratives indicate that they consider themselves informed moral agents responsible for continuing traditionality and collective identity. The culturally learned patriarchal beliefs take shape as neopatriarchy after encountering Australian society. We argue that neo-patriarchy is like an old wine in a new bottle. Women reproduce patriarchal norms, giving privileges to male authority and legitimising institutionalised gendered domination through family and marriage. This case study aims to shed light on women’s role in reproducing gender inequality in marital and family institutions. It also aims to present nuances about women’s religiosity, personal attitudes and real practices and how religious and personal perspectives are culturally constructed.